PENGARUH AKTIVITAS ORGANISASI DAN PRESTASI AKADEMIK TERHADAP KESIAPAN KERJA MAHASISWA PENDIDIKAN EKONOMI FKIP UNTAN - Jawa, Yuvensius; Asriati, Nuraini; Okianna, Okianna (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Â AbstrakThis study aims to determine the effect of organizational activities and academic pretensions on the work readiness of FKIP Untan Economic Education students. Research is causal associative research with a quantitative approach. The variables in this study are organizational activity, academic achievement, and work readiness. The source of data in this study were Economics Education students who served as Hima administrators and UKM in the FKIP Untan 2017 period of as many as 65 people. This study uses a saturated sample technique. Determination of the sample in this study must meet the active criteria in the management of the organization so that the students as many as 65 people were all sampled. The research data was collected through questionnaires and documentation. Data analysis was performed by multiple regression analysis. The results showed that there was a significant effect of organizational activity and academic achievement together on the work readiness of economic education study program students with a calculated F value of 48,133 and a significance of 0,000; there is a significant positive effect of organizational activity on the work readiness of students in economic education study programs with a tcount of 9.001 and a significance of 0.000; there is a significant positive effect of learning achievement on the work readiness of students majoring in economic education with a tcount of 2.149 and a significance of 0.036.Â Keywords: Organizational Activity, Academic Achievement, Work Readiness